SISTEM PEMERINTAHAN KERAJAAAN MAJAPAHIT - Ranti Sabariani; Retno Susanti; Hudaidah (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2025)
Majapahit is a kingdom that once existed and was located in the eastern part of Java, Indonesia which appeared around 1293-1550 AD. Majapahit kingdom has a structured government and bureaucracy based on the concept of cosmological beliefs. The king is equated with the supreme god and the center of devotion. Experienced the peak of glory during the leadership of Sri Rajasanagara or better known as Hayam Wuruk, and its decline due to external and internal problems. The purpose of writing this article aims to find out the government system and history of Majapahit.